Developing Regional Leading Products Through A Business Management Model: Evidence From Lebak Regency, Indonesia - Wahyuni (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
Regional leading products play a strategic role in strengthening local economic development and regional competitiveness. This study aims to develop regional leading products through integrated regional economic analysis and business management models in Lebak Regency, Indonesia. A descriptive-analytical approach is employed by combining qualitative and quantitative techniques. Regional economic potential is identified using Location Quotient (LQ) analysis, Klassen Classification, Shift Share, and the Growth Ratio Model (GRM), while qualitative data is collected through in-depth interviews with regional stakeholders and relevant institutions. Regional leading products play a strategic role in strengthening local economic development and regional competitiveness. This research aims to develop regional flagship products through integrated regional economic analysis and business management models in Lebak Regency, Indonesia. A descriptive-analytical approach is used by combining qualitative and quantitative techniques. Regional economic potential is identified using Location Quotient (LQ) analysis, Klassen Typology, Shift Share, and Growth Ratio Model (GRM), while qualitative data is collected through in-depth interviews with regional stakeholders and related agencies. The results show that the agriculture, manufacturing, and food service sectors are the main sectors with strong growth potential and competitive advantages. These findings provide policy implications for the local government in designing effective strategies for sustainable regional product development and economic growth.